2017
DOI: 10.1111/famp.12292
|View full text |Cite
|
Sign up to set email alerts
|

New Sexism in Couple Therapy: A Discursive Analysis

Abstract: The persistence of gender inequality in postindustrial societies is puzzling in light of a plethora of changes that destabilize it, including shifts in economy, legislation, and the proliferation of feminist politics. In family relations, such persistence manifests as a disconnect between couples aspiring to be more egalitarian yet continuing to enact traditional gender roles and hierarchies. There is an emerging consensus that gender inequality persists because of people's continued reliance on sexist ideolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In a recent discursive study (Sutherland et al, 2017), we showed how partners in intimate relationships evoked sexist notions (e.g., women are "natural" caregivers, men are not as relationally oriented as women) for specific social and rhetorical purposes. For example, one participant reported speech of other men (all the guys that I've talked to say the same thing 'what can you do, there is nothing that you can really do as a guy for the first couple of months') and produced complete unanimity among men (note the extreme case formulation "all" in all the guys).…”
Section: Implications For Therapistsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent discursive study (Sutherland et al, 2017), we showed how partners in intimate relationships evoked sexist notions (e.g., women are "natural" caregivers, men are not as relationally oriented as women) for specific social and rhetorical purposes. For example, one participant reported speech of other men (all the guys that I've talked to say the same thing 'what can you do, there is nothing that you can really do as a guy for the first couple of months') and produced complete unanimity among men (note the extreme case formulation "all" in all the guys).…”
Section: Implications For Therapistsmentioning
confidence: 95%
“…We are informed by social constructionist and postmodern feminist perspectives and have had an ongoing interest in discourse and its link to gender and power, including in the context of family therapy (Sutherland, 2007;Sutherland, LaMarre, Rice, Hardt, & Jeffery, 2016;Sutherland, LaMarre, Rice, Hardt, & Le Couteur, 2017). The first author is a family therapist and the second and third authors are gender scholars.…”
mentioning
confidence: 99%
“…Moving beyond the conflicts about epistemology that can be a block to bringing science to practice, these postmodern clinicians and researchers have begun to look at research methodologies from psychotherapy research that are most compatible with their world view applied to couple and family therapy. Thus, we have seen use of patient-focused research assessing self-reported progress (Sparks & Duncan, 2018), various methods of linguistic analysis (Ong, Barnes, & Buus, 2019;Sutherland, LaMarre, Rice, Hardt, & Le Couteur, 2017) and research centered on physiological and interpersonal processes (Laitila et al, 2019;Seikkula, Karvonen, Kykyri, Penttonen, & Nyman-Salonen, 2018). Most of all, several of these researchers have tapped into the long-standing tradition of psychotherapy process research to look at the what is happening in the therapy process, especially in terms of client and therapist experience (Laitila et al, 2019;Lambert, 2016).…”
mentioning
confidence: 99%
“…We know a good deal about the processes that help people feel anchored from family science. Attachment can be secure or insecure (Sandberg, Bradford, & Brown, ); other people can be mentalized or not (Asen & Fonagy, ); reinforcements and exchanges can be stable and unstable (Fischer, Baucom, & Cohen, ); conversation can be life enhancing or coercive and destructive (Sutherland, LaMarre, Rice, Hardt, & Le Couteur, ). Trump elicits and promotes insecure attachment even in those close to him, modeling a chaotic bullying way to others that engenders more obvious bad behavior by others.…”
mentioning
confidence: 99%